(untitled) (Journal of Additive Manufacturing Technologies, 2022)
Laser Powder Bed Fusion (L-PBF) enables the manufacturing of highly complex parts with less material consumption for being used in various industrial applications. Metal powders are commonly used as feedstock material and the powder can be reused several times. Especially in aerospace applications, the reused powder characteristics are quite important in terms of traceability over the part quality since the aerospace industry requires high-quality and reliable end-use parts. In this study, Alloy 718 metal powder, which is generally utilized in high-temperature applications in gas turbine engines due to their good creep and corrosion resistance, were characterized over a 20 series of L-PBF build cycles. The powder characterization was performed in order to investigate the flow behavior of powder reused multiple times by using several methods such as powder rheology, particle size distribution (PSD), and quantitative morphology analysis along with apparent and tap density measurements. The results showed that no major and meaningful difference was seen among 20 times reused powder in terms of PSD and their morphology whereas there is a prominent difference seen by density measurements and with shear cell measurements by powder rheology. These methods revealed that reusing powder causes worse flowability trend.